On some spectral properties of nonlocal boundary-value problems for nonlinear differential inclusion - Alama, Hameda Mohamed (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We study the solutions to the Sturm–Liouville boundary-value problem for a nonlinear differential inclusion with nonlocal conditions. The maximal and minimal solutions are demonstrated. The analysis of eigenvalues and eigenfunctions is performed. It is discussed whether multiple solutions may exist for the inhomogeneous Sturm–Liouville boundary-value problem for differential equation with nonlocal conditions.